Opinion of nurses of internal medicine wards regarding factors determining their work - observational and cross-sectional studies - Radosz-Knawa, Zuzanna; Kamińska, Alicja; Malinowska-Lipień, Iwona; Brzostek, Tomasz; Gniadek, Agnieszka (Central European journal of public health, 2023)
The aim of the study was to assess the factors determining the work of nurses in internal medicine departments. The study was multicentre, cross-sectional, and observational. The selection of the research group was intentional. The subject of the study were 209 nurses working in 11 internal medicine departments in 10 hospitals in the region of southern Poland. The number of patients cared for by one nurse, nurses' participation in the decision-making process, and nurses' age were shown to be direct predictors of emotional exhaustion. The number of patients cared for by a single nurse, nurses' participation in the decision-making process, and age were direct predictors of depersonalization. It was shown that significant (p < 0.05) independent (multivariate analysis) variables of the job satisfaction subscale were information on support for nurses at work by managerial staff and nurses' participation in the decision-making process. After analysing the impact of socio-demographic factors on the nurses' working environment, it was found that the participation of nurses in the decision-making process was significantly lower in the youngest group than in the other age groups (p = 0.006). Participation of nurses in the decision-making process is a direct determinant of occupational burnout. A higher number of patients under the care of a nurse, lack of participation in the decision-making process and a higher age of nurses are predictors of emotional exhaustion and depersonalization.